Interdisciplinary Treatment of Breast Cancer After Mastectomy With Autologous Breast Reconstruction Using Abdominal Free Flaps in a University Teaching Hospital—A Standardized and Safe Procedure - Steiner, Dominik; Horch, Raymund E.; Ludolph, Ingo; Schmitz, Marweh; Beier, Justus P.; Arkudas, Andreas (Frontiers in Oncology, 2020)
Background: Breast cancer is the most common malignancy in women. The interdisciplinary treatment is based on the histological tumor type, the TNM classification as well as the patient’s wishes. Following tumor resection and (neo-) adjuvant therapy strategies, breast reconstruction represents the final step in the individual interdisciplinary treatment plan. Although manifold flaps have been described, abdominal free flaps, such as the deep inferior epigastric artery perforator (DIEP) or the muscle sparing transverse rectus abdominis myocutaneous (ms-TRAM) flap, are the current gold standard for autologous breast reconstruction. This retrospective study focuses on the safety of autologous breast reconstruction upon mastectomy using abdominal free flaps. Methods: From April 2012 until December 2018, 193 women received 217 abdominal free flaps for autologeous breast reconstruction at the university hospital of Erlangen. For perforator mapping we performed computed tomography angiography (CTA). Venous anastomosis was standardized using a ring pin coupler system. A retrospective analysis was performed based on medical records, the surgery report and follow-up of outpatient course. Results: In most cases autologous breast reconstruction was performed as a secondary reconstructive procedure after mastectomy and radiotherapy. In total 132 ms1-TRAM, 23 ms2-TRAM and 62 DIEP flaps were performed with 21 major complications (10 %) during hospital stay including 5 free flap losses (2.3 %). In all cases of free flap loss, we found an arterial thrombosis as the main cause. In 24 patients a bilateral breast reconstruction was performed without free flap loss. The majority of free flaps (96.7 %) did not need additional super- or turbocharging to improve venous outflow. Median venous coupler size was 2.5 mm [range 1.5 – 3.5 mm]. Conclusion: Using CTA and venous coupler systems, autologous breast reconstruction with DIEP or ms-TRAM free flaps is a safe and standardized procedure in high volume microsurgery centers.